Vegetation Analysis in Community Forests of Terai Region, Nepal - Joshi, Rajeev; Chhetri, Ramesh; Yadav, Karan (International Journal of Environment, 2019)
This paper deals with the study of vegetation analysis of tree species in Ganesh and Ramnagar community forests (CF) of the Terai region. For the study, altogether 63 concentric sample plots (each plot of 500 m2) were laid using systematic sampling with a sampling intensity of 0.5%. A total of 967 individual trees representing 16 different tree species were identified. Both CF was dominated by monospecies such as Mallotus philippensis (Ganesh CF) and Shorea robusta (Ramnagar CF) based on the Importance Value Index (I.V.I). Likewise, the Shannon-Wiener diversity index was higher in Ganesh CF whereas the dominance index was low. Similarly, the index of evenness and richness was also slightly higher in Ganesh CF than Ramnagar CF. The study provided information about the structure, composition, and dominance of tree species which is essential for conservation and sustainable management of community forests. Therefore, this article serves as an example of establishing community forests so as to initiate the conservation and preservation of local biodiversity.